2014
DOI: 10.1007/s10942-014-0200-9
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Rational Emotive Behavior Therapy (REBT) on the Irrational Beliefs of Blue-Chip Professionals

Abstract: The extant literature reveals a scarcity of research applying rational emotive behavior therapy (REBT) in business settings. Against the backdrop of severe market conditions and inevitable involuntary job loss, the application of psychological interventions to reduce mental and physical health issues is highly pertinent and potentially valuable. This paper reports the effects of an intensive REBT programme on the irrational beliefs of staff undergoing redundancy from a Blue-Chip organisation. A repeated-measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Secondary beliefs are derived from the primary belief (Dryden, 2012). The goal of REBT is to reduce irrational beliefs in favour of rational beliefs.Researchers have applied REBT to develop functional emotions and effective performance in contexts such as competitive sport (Turner, 2014;Turner & Barker, 2013) and business (Turner & Barker, 2015). However, one limitation hindering research developments in performance settings is the lack of a contextually-specific irrational beliefs measure that is short enough for test-retest purposes and aligns closely with contemporary measures, so that a more accurate understanding of the specific conditions or subpopulation with which a tool works best in can be gained.…”
mentioning
confidence: 99%
“…Secondary beliefs are derived from the primary belief (Dryden, 2012). The goal of REBT is to reduce irrational beliefs in favour of rational beliefs.Researchers have applied REBT to develop functional emotions and effective performance in contexts such as competitive sport (Turner, 2014;Turner & Barker, 2013) and business (Turner & Barker, 2015). However, one limitation hindering research developments in performance settings is the lack of a contextually-specific irrational beliefs measure that is short enough for test-retest purposes and aligns closely with contemporary measures, so that a more accurate understanding of the specific conditions or subpopulation with which a tool works best in can be gained.…”
mentioning
confidence: 99%
“…Turner and Barker studied REBT effects upon irrational believes among blue-chip professional's base on results, post-test stage indicated significant decreasing in irrational believes, need to achievement and justice demand than pre-test stage. 25 Ellis and Joffe found that by participating at REBT sessions, 40 persons stated that their thought. The disturbance was improved, 48 persons responded better to their problems, 58 persons stated that have disturbance feeling, 26 persons have found more risk ability, 23 persons stated that success in their days' affairs and 24 persons showed their feelings and reactions.…”
Section: Discussionmentioning
confidence: 99%
“…22 This scale consists of 25 items; every 5 items has known as one subscale. These 5 subscales consist of: self-appraisal, gathering career information, goal selection, planning, and problem-solving, person's opinions scored by 5-degrees scale from "I'm not sure at all" until "I'm sure completely" the scores range have been 25 22 Bavi and colleagues 23 reported internal conformity coefficient of this test by Cronbach α = 0.93. Sadeghi stated questionnaire reliability coefficient by Cronbach α = 0.89.…”
Section: Career Decision Self-efficacymentioning
confidence: 99%
“…In line with REBT's hypothesis, a number of studies have offered the empirical evidence on the association between irrational beliefs and dysfunctional emotions (Brown, Dowd, & Freeman, 2010) as well as the correlation between irrational beliefs and maladaptive behaviours (Szentagotai & Jones, 2010;Turner & Barker, 2015). According to David, Montgomery, Macavie, Bovbjerg, Macavie, and Bovbjerg (2005) and Dryden (1999), there are four main categories of irrational beliefs which are demandingness, awfulizing or catastrophizing, global evaluation or self-downing and low frustration tolerance.…”
Section: Introductionmentioning
confidence: 98%
“…REBT posits that people always mistakenly blame external events for their unhappiness (Ellis, 1994). In the face of adversity, it is the belief about the situation but not the situation itself that leads to emotional disturbances (Ellis, 1994;Turner & Barker, 2015). In REBT, beliefs are at the core of individuals' emotions and behaviours (Dryden and Branch, 2008).…”
Section: Introductionmentioning
confidence: 99%